QUIZIZZ EFFECT ON STUDENTS’ GRAMMAR MASTERY IN HIGHER EFL CLASSROOM BASED MOBILE ASSISTED LANGUAGE LEARNING (MALL) - Dewi, K.S.; Myartawan, I.P.N.W.; Swari, N.K.T.A.; Sugihartini, N. (Language and Education Journal Undiksha, 2020)
This research aimed at investigating the effect of MALL strategy through Quizizz applicationtowards the students’ grammar mastery in higher education level. The design of this research was aquasi-experimental research with post-test only control group design. This research population wasthe 4th semester which consists of 246 students in English Language Education UNDIKSHA. Thesampling technique of this research was cluster random sampling. The sample was 33 students of FClass as the experimental group who was taught by using MALL strategy through Quizizz and 32students of C class as the control group who was taught by using conventional strategy. This resultwas also supported by the calculation result of effect size which was 0.92 that belongs to the largesteffect. The large result of the effect size proven that the use of MALL strategy through QuizizzAplication was appropriate for teaching grammar especially in higher education level.